Artificial intelligence and its effects on critical thinking and problem-solving abilities in higher education - Aprianto, Ide; Sofyan; Rahmawati, Sophia; Sufyadi, Susanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The urgency of this research lies in the need to critically examine how the integration of Artificial Intelligence, particularly ChatGPT, influences the development of higher-order cognitive skills, ensuring that technological advancement in higher education aligns with the goals of meaningful and reflective learning. This study aims to analyze the impact of Artificial Intelligence (AI), particularly ChatGPT, on the critical thinking and problem-solving abilities of students in the Department of Education at the Faculty of Teacher Training and Education, Jambi University. A quantitative method with an ex post facto approach was employed. The research involved 855 students from the Department of Education at Jambi University, with a sample of 207 respondents selected using purposive sampling based on their active use of ChatGPT for more than two months. Data were collected through a structured questionnaire and analyzed using SmartPLS version 4.0.9.9 to test the validity, reliability, and research hypotheses. The results reveal that the use of AI-based ChatGPT has a significant positive effect on both students' critical thinking and problem-solving skills, both individually and simultaneously. The study recommends that higher education institutions integrate AI tools like ChatGPT within reflective and guided learning frameworks to enhance students’ cognitive engagement and critical inquiry.